E-LEARNING: DEVELOPMENT VECTOR - Alexandr V. Solovov; Anastasia A. Men'shikova (Высшее образование в России, 2016)
The article addresses a number of areas of e-learning development: using mobile devices, the massive open online courses, computer simulation, automation systems, professional activities, computer games, the concept of a SMART education system, knowledge management. The authors discuss the factors that stimulate implementation of these innovations in education, the positive and negative aspects of their use, provide guidelines for improving the didactic effectiveness of these innovations.